SETTLEMENT OF DISPUTES OVER BREACH OF CREDIT AGREEMENTS BETWEEN LIMITED LIABILITY COMPANIES AND BANK WITH LAND GUARANTEE - Lumassia; Sefullah; Budiman, Anwar (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
The Power of Attorney to Impose Mortgage Rights (SKMHT) holds a significant position in credit agreements as a binding instrument for mortgage rights guarantees. In this context, the SKMHT serves as a tool to provide legal protection to the creditor's rights over the guarantee. This research employs a juridical-empirical approach, with descriptive analytical specifications. The data sources and types used in this study include primary data in the form of interviews and secondary data, namely primary legal materials, secondary legal materials, and tertiary legal materials. The field research data collection techniques consist of interviews and literature research using legal protection theory and legal certainty theory. The data analysis of this research uses qualitative methods, and from the results of the data analysis that has been collected, conclusions are drawn using inductive reasoning and presented in the form of legal writing. The results of the study indicate that 1) The position of the Power of Attorney to Impose Mortgage Rights (SKMHT) in the credit agreement as a binding guarantee for mortgage rights is very important. The SKMHT functions as a legal instrument that provides legal certainty for creditors and debtors in credit agreements. The SKMHT strengthens the mortgage rights guarantee by granting power to the creditor to register the mortgage rights on the guarantee object. In the context of legal protection, the SKMHT protects the interests of creditors and debtors and ensures balance and justice between the two. 2) In the implementation of the imposition of mortgage rights with the Power of Attorney to Impose Mortgage Rights (SKMHT) based on Law Number 4 of 1996, there are several obstacles that can disrupt legal certainty. Some of these obstacles include ambiguity or deficiencies in the preparation of the SKMHT, administrative problems in the registration process, rejection or obstacles from the Land Office. To overcome these obstacles, several solutions need to be implemented, such as drafting a clear and accurate SKMHT, improving the efficiency of the registration process, clarifying regulations and communication with the Land Office, an effective monitoring and supervision system, as well as counseling and education to related parties.